The mediating role of job satisfaction in the effect of leader-member exchange on burnout: A study on physical education teachers - Duyan, Mehdi (Afyon Kocatepe Üniversitesi)
This research was carried out to examine the mediating role of job satisfaction in the effect of physical education teachers' leader-member exchange on burnout. Liden and Maslyn's (1998a) leader-member exchange, Chang and Chang's (2007) job satisfaction, and Maslach and Jackson's (1981)Maslach burnout scale were used as data collection tools to determine the level of leader-member exchange. The study group of the research consists of a total of 155 physical education teachers, who work in the Malatya and Hatay provinces of Turkey. The study group was selected with the convenience sampling method, one of the non-random sampling methods. A questionnaire was applied to the teachers participating in the research via electronic communication tools. Data from participants were analyzed using SPSS Amos 20.0. In the research, descriptive statistics, correlation and boostrap regression analysis were performed. As a result of this study, it was found that job satisfaction played a mediating role in the effect of leader-member exchange on physical education teachers' burnout levels. It can be stated that increasing physical education teachers' leader-member exchange and improving their relationships with their superiors can be effective in increasing job satisfaction and reducing burnout.

Bu araştırma, Beden Eğitimi Öğretmenlerinin lider-üye etkileşiminin tükenmişlik üzerindeki etkisinde iş tatminin aracı rolünü incelemek amacıyla yapılmıştır. Veri toplama araçları olarak lider-üye değişimi, iş tatmini ve Maslach tükenmişlik ölçeği kullanılmıştır. Araştırmanın çalışma grubunu Türkiye’nin Malatya ve Hatay illerinde görev yapan toplam 155 Beden Eğitimi Öğretmeni oluşturmaktadır. Çalışma grubu, tesadüfi olmayan örnekleme yöntemlerinden biri olan kolayda örnekleme yöntemi ile seçilmiştir. Araştırmaya katılan öğretmenlere elektronik iletişim araçları aracılığıyla anket uygulanmıştır. Katılımcılardan elde edilen veriler SPSS Amos 20.0 ve Process makro kullanılarak analiz edilmiştir. Araştırmada tanımlayıcı istatistikler, korelasyon, doğrulayıcı faktör analizi ve bootstrap regresyon analizi yapılmıştır. Bu çalışma sonucunda lider-üye etkileşiminin Beden Eğitimi Öğretmenlerinin tükenmişlik düzeylerine etkisinde iş tatminin aracılık rolü olduğu tespit edilmiştir. Beden Eğitimi Öğretmenlerinin lider-üye etkileşimini artırmanın ve üstleriyle ilişkilerini geliştirmenin iş tatminini artırmada ve tükenmişliği azaltmada etkili olabileceği ifade edilebilir.
Lider-Üye etkileşiminin tükenmişlik üzerindeki etkisinde iş tatminin aracı rolü: Beden eğitimi öğretmenleri üzerine bir araştırma
Keywords: Leader-Member Exchange; Job Satisfaction; Burnout; Physical Education Teacher; Lider-Üye Değişimi; İş Tatmini; Tükenmişlik; Beden Eğitimi Öğretmeni